A Case-by-Case Comparison of the Classification of Law Enforcement and Vital Statistics Data on Homicide - Regoeczi, Wendy C. (2006)
This study uses data from the California Linked Homicide File as a basis for evaluating the validity and reliability of homicide data. Case-by-case comparisons of variables reported by both agencies indicate that agreement between law enforcement and vital statistics data is highest with classifying homicides and victim gender and race and lowest with classifying victim age, manslaughters, and police justifiable homicides. The findings from a multilevel analysis examining what types of cases are unable to be linked over the two data-collection systems reveal that homicides involving Hispanic victims, weapons other than handguns, and family members other than intimate partners and homicides involving felonies, other nonfelonies, and negligent manslaughters have a greater likelihood of not being matched across the agencies. Death investigation systems that use medical examiners also decrease matching. The need for qualitative research examining how classification decisions are made by police and medical examiners or coroners is discussed